Pengaruh Promosi dan Transparansi Pengelolaan Zakat Terhadap Minat Zakat pada Lembaga Amil Zakat Infaq dan Shadaqah UPZIS LAZISNU Cangkring - Nisa, Zumrotun; ', syuhada; ayu, intan; Fauziyah, Nina Rohmatul (Fakultas Agama Islam, 2025)
This research was made with the aim of knowing the effect of promotion and transparency of zakat management in Cangkring village on zakat interest partially or simultaneously. As for the background, the researcher is interested in making this thesis based on the results of observations and observations made, where the authors found indications of effectiveness that were not optimal, because many members had side jobs such as being teachers, farmers and so on. The method used is a quantitative method, In this study the data obtained were secondary data and primary data with data collection techniques using questionnaires, validity and reliability tests, classical assumption tests, multiple linear regression tests and hypothesis testing. The results of this study indicate that there is no effect of the promotion variable on the interest in zakat while the transparency variable has an influence on the interest in zakat in Cangkring village, From the results of the T (partial) test, promotions get a value of (-1.006), and the transparency variable gets a value of (3.249), which is greater than ttable (1.672). Meanwhile, from the results of the F test (simultaneous) both variables get a value of (5.435) which is greater than ftable (2.540).